2020
DOI: 10.1007/s12032-020-01397-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase II prospective trial “Give Me Five” short-term high precision radiotherapy for early prostate cancer with simultaneous boost to the dominant intraprostatic lesion: the impact of toxicity on quality of life (AIRC IG-13218)

Abstract: Phase II prospective trial "Give Me Five" short-term high precision radiotherapy for early prostate cancer with simultaneous boost to the dominant intraprostatic lesion: the impact of toxicity on quality of life (AIRC IG-13218) Extreme hypofracyionation: impact on QoL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…Also, in the "FLAME" trial, Kerkmeijer et al [18] proved that focal boosting the DIL up to 95 Gy in a conventional radiotherapy scheme for 264 patients (vs. 271 patients in the arm without focal boost) improved bDFS and PFS without any relevant additional toxicity. In addition, the preliminary results reported by Marvaso et al [20] in the "GIVE ME FIVE" trial reported very low acute RTOG GU and GI toxic (G2 4.69% and 1.56%, respectively, and only one patient with GU G3 at 6 months) when a dose escalation to 37.5 Gy in 5 fractions was applied as a SIB to the DIL with the VERO ® system.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, in the "FLAME" trial, Kerkmeijer et al [18] proved that focal boosting the DIL up to 95 Gy in a conventional radiotherapy scheme for 264 patients (vs. 271 patients in the arm without focal boost) improved bDFS and PFS without any relevant additional toxicity. In addition, the preliminary results reported by Marvaso et al [20] in the "GIVE ME FIVE" trial reported very low acute RTOG GU and GI toxic (G2 4.69% and 1.56%, respectively, and only one patient with GU G3 at 6 months) when a dose escalation to 37.5 Gy in 5 fractions was applied as a SIB to the DIL with the VERO ® system.…”
Section: Discussionmentioning
confidence: 96%
“…In our center at the European Institute of Oncology (IEO) IRCCS, Milan, Italy, a high level of expertise has been achieved in the setting of PCa UH-RT, counting more than one thousand patients treated with very low treatment-related toxicities reported [20]. In addition, data for patients receiving UH-RT and simultaneous integrated boost (SIB) on the DIL at IEO has already been published, demonstrating the safety and effectiveness of this treatment [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…SABR has been predominantly explored in low-and intermediaterisk prostate cancer patients, yielding excellent outcomes 10,19,20,21] However, several interrogations persist concerning the optimal dose, target volumes and timing. Interestingly, a relevant question that needs further exploration is the effectiveness of SABR in high-risk patients, especially given the limited number of studies addressing this particular aspect [7,9,11,12,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The planning target volume of the prostate (PTV-P) was established by applying a systematic expansion of 5 mm in all the directions, except for a 3 mm expansion posteriorly. Similarly, for the planning target volume of the dominant intraprostatic lesion (PTV-DIL), a uniform expansion of 3 mm in all directions was added to CTV-DIL [ 23 ].…”
Section: Case Reportmentioning
confidence: 99%